2021
DOI: 10.3390/s21093045
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Imaging for Bloodstain Identification

Abstract: Blood is key evidence to reconstruct crime scenes in forensic sciences. Blood identification can help to confirm a suspect, and for that reason, several chemical methods are used to reconstruct the crime scene however, these methods can affect subsequent DNA analysis. Therefore, this study presents a non-destructive method for bloodstain identification using Hyperspectral Imaging (HSI, 397–1000 nm range). The proposed method is based on the visualization of heme-components bands in the 500–700 nm spectral rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Oxyhemoglobin and methemoglobin perform characteristic peaks in the visible light spectrum, marked as b (542 nm) and a (576 nm), which detect blood and differentiate it from other substances. 5 Zulfiqar et al 6 proposed an HSI-based experimental protocol able to differentiate bloodstains from other substances similar in colour and consistency (ketchup, rust-coloured acrylic paint, red and brown acrylic paint, red and rust nail polish, fake blood and red ink) on different substrates (white cotton fabric, white tiles and PVC sheet); besides, the samples were examined for three days to investigate their behaviour over time. The authors concluded that the proposed method achieved the best results.…”
Section: Bloodstain Analysismentioning
confidence: 99%
“…Oxyhemoglobin and methemoglobin perform characteristic peaks in the visible light spectrum, marked as b (542 nm) and a (576 nm), which detect blood and differentiate it from other substances. 5 Zulfiqar et al 6 proposed an HSI-based experimental protocol able to differentiate bloodstains from other substances similar in colour and consistency (ketchup, rust-coloured acrylic paint, red and brown acrylic paint, red and rust nail polish, fake blood and red ink) on different substrates (white cotton fabric, white tiles and PVC sheet); besides, the samples were examined for three days to investigate their behaviour over time. The authors concluded that the proposed method achieved the best results.…”
Section: Bloodstain Analysismentioning
confidence: 99%
“…When comparing a Crime-lite ® ML2 ALS instrument (Foster and Freeman Ltd., Evesham, UK) and HIS-NIR imaging using an SWIR3 hyperspectral camera working in the 1000-2500 nm spectral range (Specim Ltd., Oulu, Finland) [66], the resultant images obtained from the HIS-NIR imaging were shown to be superior at revealing the location of body fluid staining in known reference samples, simulated casework samples and on unknown staining on forensic exhibits. Using blood samples and different substrates, spectra were generated [67] that were used to train different classifiers to detect aged bloodstains and most recently a "blood detection dataset" was produced [68] specifically to assist in the challenging task of algorithm development for this new technology.…”
Section: Alternative Light Sourcesmentioning
confidence: 99%
“…The experiments showed that deep learning can indeed outperform classical machine learning in blood stain classification, especially in the more challenging multiple-image scenario. Blood identification was also tackled by Zulfiqar et al, and the authors suggested a new method based on the visualization of heme-components bands in the 500–700 nm spectral range [ 34 ]. In their algorithm, Savitzky Golay filtering is used to highlight the subtle bands of all samples.…”
Section: A Brief Review Of the Articles In The Special Issuementioning
confidence: 99%